FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN RESIKO JATUH PADA LANSIA DI BPPLU KOTA BENGKULU TAHUN 2017 - Ramlis, Ravika (UNIVED Press, Universitas Dehasen Bengkulu, 2018)
The incidence of falls in the elderly group may cause injury to the soft tissues and fractures of the thigh or wrist and even result in death. In addition, the State also can cause a variety of health problems including: pain, physical discomfort, the limitations of mobilization, and the slow healing process so that it will have an impact towards kondisilansia, where they will experience the problem of addiction to perform daily activities.Research methods the research design used was descriptive analytic. The study tried to gather information on factor-related risk factors for falls in the elderly include factor intrinsic, extrinsic, and circumstantial. The sample in this study is the whole elderly in BPPLU city of Bengkulu , namely an amount of 60 people. The method of sampling in this research are the total sampling.The results showed that there is a relationship between the intrinsic risk factors for falls in the elderly in Bengkulu City Year 2017 BPPLU. There is a relationship between extrinsic factors with risk of falls in the elderly in Bengkulu City Year 2017 BPPLU. Researchers suggest to the BPPLU can be a cornerstone of the implementation of the programme of activities, coaching, guidance and counseling in an attempt to increase knowledge about the factors factors that are associated with the risk of falls in the elderly.